ANALISIS RISIKO PRODUKSI PADA AKTIVITAS EKSPOR KOPI DI SUMATERA UTARA - Dita Deviana Fadhilah; Sriwardany (Institute of Computer Science (IOCS), 2023)
Indonesia's coffee export value in 2021 occupied the thirteenth position as a world coffee exporter country. Sumatra Utara is classified as one of the coffee-producer regions on the Sumatra island, this area has international trade routes through the Belawan Port hub. The proof is also that there are risks in the agribusiness coffee, from upstream to downstream. Risk management is important to keep the coffee commodity contributing to the economy. This study is intended to analyze production risks in coffee export activities in Sumatra Utara. The data analyzed is in the form of primary data obtained through interviews with thirty respondents. Meanwhile, secondary data was obtained through related institutions and the media. Data is analyzed to obtain priority risks in coffee export production activities using the Risk Priority Number calculation. The design of this study was made with reference to the concept of risk management according to ISO 31000. From the results of the identification, it can be seen that the risk of production can occur due to factors in the coffee plant and processing activities carried out after harvesting. There are seven sources of production risk in coffee factories and ten sources of production risk in post-harvest production processes. Through the calculation of the Risk Priority Number, it is known that there are three main priority risks in coffee plant factors and the five highest priority risks in export coffee production activities. The highest priority found was on the quality of the coffee beans.